2002
DOI: 10.1021/jf011552j
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tobacco-Specific Nitrosamines in Moldovan Cigarette Tobacco

Abstract: Tobacco-specific nitrosamines (TSNA) are among the most important and abundant strongly carcinogenic agents in unburned tobacco. It has been established that 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) induces lung tumors in rodents independent of the route of administration. N'-Nitrosonornicotine (NNN) causes tumors of the esophagus and nasal cavity in rats, lung in mice, and respiratory tract in hamsters. Although the manufacturing of cigarettes is an important domain of Moldovan industry, there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…This is in agreement with a recent study conducted in 31 other countries, which showed that American cigarettes had significantly higher tobacco TSNA levels than did all locally popular non-U.S. brands (25). However, TSNA levels in Moldovan cigarette tobacco varied widely and in some Moldovan brands were similar to those in American cigarettes (24).…”
Section: Introductionsupporting
confidence: 91%
“…This is in agreement with a recent study conducted in 31 other countries, which showed that American cigarettes had significantly higher tobacco TSNA levels than did all locally popular non-U.S. brands (25). However, TSNA levels in Moldovan cigarette tobacco varied widely and in some Moldovan brands were similar to those in American cigarettes (24).…”
Section: Introductionsupporting
confidence: 91%
“…Tobacco-specific nitrosamines analyses was carried out by a slight modification of a method described previously by Stepanov et al 20 Five-hundred milligram of humidity-conditioned tobacco and 10 mL of citrate-phosphate buffer (pH ¼ 4.5) containing ascorbic acid were added to a 30 mL Nalgene centrifuge tube (Nalge Nunc International, Rochester, NY). Two-hundred nanograms of 5-MeNNN (internal standard for NNN, NAT, and NAB) and C5-NNK (internal standard for NNK) were added.…”
Section: Tobacco Analysesmentioning
confidence: 99%
“…20 Fifty milligrams of humidity-conditioned tobacco and 20 mL of methanol containing 50 mg of KOH were added to 30 mL Nalgene centrifuge tubes. The samples were homogenized (Polytron) and then sonicated for 3 hr.…”
Section: Tobacco Analysesmentioning
confidence: 99%
“…Several methods, including gas chromatography(GC) [3−5] , highperformance liquid chromatography(HPLC) [6] , gas chromatography/mass spectrometry(GC/MS) [7] and gas chromatography coupled with thermal energy analyzer (TEA) [8] , have been used to analyze TSNAs. Among these methods, GC coupled with TEA which offers reasonable sensitivity and is nitroso-specific, is the most commonly used method.…”
Section: Introductionmentioning
confidence: 99%